The effects and implications of Kazakhstan's adoption of international financial reporting standards : a resource dependence perspective - Kim, Oksana; Vlady, Svetlana (Stuttgart, Germany : Ibidem Press, 2017)
"Despite having an underdeveloped supporting infrastructure and limited resources, Kazakhstan was the first CIS country to require international financial reporting standards in 2004 for banks, and in 2005 for all public companies. What were the economic consequences of this important reform' In the 1990s, Kazakhstan's capital market reforms mirrored those of Russia due to the two countries' cooperating mode driven by a high level of resource interdependence and environmental uncertainty, following the collapse of the Soviet Union. Yet, by 2003, dependence on external donors (the IMF, World Bank) took precedence over interdependence with Russia. As a result, Kazakhstan unilaterally proceeded with adoption of IFRS, while Russia backed up from this initiative. This study reports that Kazakhstan's inflow of foreign direct investments was the greatest among the CIS nations following the adoption of IFRS. In addition, in 2005'11, Kazakhstani public firms' reporting quality was higher than that of the Russian public firms operating in a similar environment but exempt from the IFRS reporting requirement. Kazakhstan was the first CIS nation to repay its external debt ahead of schedule and to receive an investment grade from Moody's rating agency. The book concludes that Western-style capital market reforms'in this emerging market with a not-so-distant communist past'had significantly positive outcomes."
List of tables -- List of figures -- Foreword by Svetlana Vlady -- Introduction -- Background information -- Kazakhstan's history and development after the collapse of the Soviet Union -- Capital market reforms and adoption of International Financial Reporting Standards (IFRS) in Kazakhstan -- National stock market system -- Adoption of International Financial Reporting Standards (IFRS) in Kazakhstan -- Global adoption of IFRS -- History behind the global movement to adopt a uniform set of accounting standards and the evolvement of IFRS -- Empirical evidence regarding implementation of IFRS : economic and legal explanations to the degree of success of IFRS adoption -- Alternative explanations to the IFRS adoption consequences, not limited by legal and economic arguments : evidence regarding the IFRS adoption benefits for CIS countries -- Resource dependence theory and its application to Kazakhstan's strategic decision to become the first and early adopter of IFRS within the CIS -- The main provisions of the resource dependence theory -- Application of the resource dependence theory to Kazakhstan's strategic decision to become the first adopter of IFRS within the CIS -- Empirical analyses -- Value relevance of reported information in the post-adoption period -- Comparison of value relevance of reported information for Kazakhstani and Russian public firms -- Examining changes in market efficiency over time, before and after IFRS adoption, using the KASE index -- Autocorrelation test -- The unit root test -- Kazakhstani blue chips cross-listed in London : the market reaction to the cross-listing event -- Future perspectives -- Kazakhstan's success and future perspectives -- The future of the IFRS reporting practices in Kazakhstan -- Conclusions -- Bibliography.
eBooks on EBSCOhost
Keywords: Accounting -- Standards -- Kazakhstan; Financial statements -- Standards -- Kazakhstan; Comptabilité -- Normes -- Kazakhstan; LAW -- Administrative Law & Regulatory Practice; Accounting -- Standards; Financial statements -- Standards; Kazakhstan